Having a gander at goose behaviour. Evaluating time-activity of captive and wild geese at two different wetland sites - Rose, Paul; Roper, Amelia; Giorgio, Christopher; Thomas, Joe; Kelly, Robert; O’Brien, Michelle F. (Applied animal behaviour science, 2025)
Geese are not common subjects for behavioural investigation in zoological facilities, despite their popularity in waterfowl collections and their complex ecological needs. This research evaluated time-activity budgets of six goose species located at two UK Wildfowl & Wetland Trust (WWT) centres, comparing captive population behaviours with two species of wild goose. Using a standardised ethogram and instantaneous focal sampling, we recorded over 220 h of behavioural data across 892 observations. All data were recorded in spring and summer of 2015, 2017 and 2018. Data were analysed using linear mixed models and zero-inflated models to account for high frequencies of zero occurrences in alert and social behaviours. Results show that whilst captive and wild geese broadly perform similar species-typical behaviours, captive birds exhibited higher levels of resting and lower social engagement. Foraging and locomotion differed significantly by species, and this may be a factor of ecological niche. Minimal stereotypic behaviour (<2 % of observations) was recorded in the captive birds, suggesting that the large, naturalistic enclosures provided by WWT support positive welfare by enabling appetitive behaviours, such as grazing. However, high inactivity rates highlight the need for further enrichment and dynamic enclosure management to be considered to further improve goose behavioural diversity. Comparisons with wild geese provide useful benchmarks for evaluating behavioural normality under human care. This research supports the use of time-activity budgets as a practical tool for developing evidence-based, species-specific husbandry guidelines. We recommend future research focusses on long-term, individual-bird behavioural monitoring, seasonal comparisons, and the incorporation of personality profiling to further our understanding of how geese respond to their captive care at the population, species and individual bird level. [Display omitted] •Captive and wild geese can display similarities in their time-activity.•Resting behaviour was generally higher in captive geese.•Social interaction was lower in captive geese than wild birds.•Abnormal repetitive behaviours were negligible to non-existent in performance.•Temporal and weather influences on goose time budgets were noted.